Development of Islamic Mobile Learning for Indonesian High Schools: Bridging Traditional and Digital Education through an Android-Based Platform - Fazar, Fahmi; Supriadi, Udin; Anwar, Saepul (Mimbar Agama Budaya, 2025)
This study explores the development and evaluation of the Islamic Mobile Learning (IML) application, which is designed as a supplement for students in studying Islamic Religious Education (PAI) in high schools in Indonesia. The Research and Development (R&D) approach is used combined with the ADDIE model, this study focuses on creating learning media in the form of user-friendly Android-based applications by integrating interactive multimedia features, such as quizzes, videos, and animations. This application has been validated by material experts and media experts as well as pretest-post-test assessments, very high reliability was achieved (Cronbach's Alpha = 0.989) accompanied by validity (Pearson Correlation> 0.7). The research findings show a significant increase in student learning outcomes after using the IML application and positive feedback from them as users. Although there are challenges regarding accessibility and scalability, the results indicate that the IML application offers a promising learning media as a supplement to Islamic Religious Education learning, making it more attractive, user-friendly, easily accessible, and adaptable to diverse learning environments.